1990
DOI: 10.1002/ajp.1350220205
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of serum estradiol and progesterone concentrations to the enzyme immunoassay measurements of urinary estrone conjugates and immunoreactive pregnanediol‐3‐glucuronide in Macaca mulatta

Abstract: Paired urine and serum samples from four conceptive and six nonconceptive ovarian cycles of seven adult Macaca mulatta were analyzed by radioimmunoassay (RIA) for circulating estradiol (E,) and progesterone (Po), and urinary estrone conjugates (E,C) and immunoreactive preganediol-3-glucuronide (iPDG) using enzyme immunoassay (EIA). Nonconceptive cycles exhibited a fivefold increase in urinary E,C and serum E2 levels from follicular phase levels to the preovulatory peak. Linear correlation between urinary E,C a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 17 publications
5
52
1
Order By: Relevance
“…In addition, all of these have significant crossreactivity with the assay's antibody (Shideler et al, 1991). Previous studies with domestic sheep have shown that, although this species produces increasing quantities of estrogens throughout the entire preg-nancy, the primary metabolites are probably a nonreactive diconjugate of some sort rather than the collective E 1 C conjugates (Lasley, pers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, all of these have significant crossreactivity with the assay's antibody (Shideler et al, 1991). Previous studies with domestic sheep have shown that, although this species produces increasing quantities of estrogens throughout the entire preg-nancy, the primary metabolites are probably a nonreactive diconjugate of some sort rather than the collective E 1 C conjugates (Lasley, pers.…”
Section: Discussionmentioning
confidence: 99%
“…Fecal extracts were assayed by EIA for progesterone metabolites related to PdG and estradiol metabolites, for estrone conjugates (E 1 C) as described by Shideler et al (1991), and for immunoreactive pregnanediol-like progesterone metabolites (iPdG) as described by Kirkpatrick et al (1991). Quantities of fecal extracts were 20 l for PdG and iPdG and 40 l for E 1 C. Assays were validated for bighorn sheep by means of testing halving dilutions for parallelism to the standard curve.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were analyzed for E1C and PdG following established protocols [Shideler et al, 1990;Munro et al, 1991;Valeggia et al, 1999]. Hormone values were corrected by specific gravity to account for differences in hydration status [Anestis et al, 2009].…”
Section: Assays Of Hormone Profilesmentioning
confidence: 99%
“…Growing evidence from captive studies and from long-term studies in the wild indicates that postmenopausal nonhuman primate females are common (Semnopithecus entellus [Borries et al, 1991;Sommer et al, 1992]; Pan troglodytes schweinfurthii [Nishida et al, 2003]; Macaca mulatta [Small, 1984]; Papio anubis [Strum and Western, 1982]; Cercocebus albigena [Waser, 1978]), but their postreproductive lifespans are short compared to those of humans [Pavelka and Fedigan, 1991;Caro et al, 1995;Hawkes et al, 1998]. To characterize sex hormone profiles, the metabolites most commonly used in primates are estradiol, estrone conjugates (E1C), progesterone and pregnanediol-3α-glucuronide (PdG), depending on the species [Shideler et al, 1990[Shideler et al, , 1993Lasley and Savage, 2007]. In several studies of nonhuman primates, urine samples were collected in order to evaluate hormonal profiles, estimation of the duration of the ovulatory cycle (DOC) and sexual behaviors, both in wild and captive status conditions (Cebus apella [Nagle and Denari, 1983;Carosi et al, 1999]; Saguinus oedipus [Ziegler et al, 1993]; Callimico goeldii [Jurke et al, 1994]; Pithecia pithecia [Savage et al, 1995]; Callicebus moloch [Valeggia et al, 1999]; Alouatta seniculus [Herrick et al, 2000]; Ateles geoffroyi [Campbell et al, 2001]; Callithrix geoffroyi [Mustoe et al, 2012]; P. troglodytes schweinfurthii [Emery-Thompson, 2005]; Pan troglodytes verus [Stumpf and Boesch, 2005]; Rhinopithecus roxellana [Yan and Jiang, 2006]; Colobus guereza [Harris and Monfort, 2006]; Gorilla beringei beringei [Habumuremyi et al, 2014]).…”
Section: Introductionmentioning
confidence: 99%